Takdir dan Usaha Manusia dalam Al-Qur'an dan Relevansinya terhadap Fatalisme Umat Islam: Analisis Interpretasi QS. Ar-Ra'd ayat 11 - Muhammad Zulhan Hasibuan; Ahmad Zuhri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
A fatalistic understanding of the concept of destiny (al-qadar) has resulted in a passive attitude that weakens the work ethic and orientation of social transformation of Muslims. This study aims to analyze the concept of destiny and human effort in the Qur'an through a thematic interpretation approach (tafsir maudhu'i) to QS. ar-Ra'd (13):11 and examine its relevance to the contemporary phenomenon of fatalism. Using qualitative literature methods, this study analyzes three books of interpretation, al-Tabari, Sayyid Qutb, M. Quraish Shihab, using comparative linguistic-semantic analysis. The results of the study show, (1) the concept of destiny is integrative and cannot be understood as absolute determinism. (2) QS. ar-Ra'd (13):11 contains three fundamental principles of moral causality, human initiative, and collective responsibility. (3) the phenomenon of fatalism includes three theological, social, and psychological typologies that originate from partial interpretations. The novelty of this research lies in the integration of linguistic analysis of three key vocabularies, the typology of fatalism, and three operational paradigmatic shifts as a theological response to fatalism.